Autism - Murray, Stuart (New York : Routledge, 2012)
'Autism is the first book on the condition that seeks to combine medical, historical and cultural approaches to an understanding of the condition. Its purpose is to present a rounded portrayal of the ways in which autism is currently represented in the world, It focuses on three broad areas: the facts of scientific research, including new ideas surrounding research into genetics and neuroscience, as well as the details of diagnosis and therapy; the history of the condition as it developed through psychiatric approaches to the rise of parent associations, neurodiversity and autism advocacy; and the fictional and media narratives through which it is increasingly expressed in the contemporary moment. Accessible and written in clear English, Autism is designed for student audiences in English, Disability Studies, Cultural Studies, History, Sociology, and Medicine and Health, as well as medical practitioners and the general reader. Autism is a condition surrounded by misunderstanding and often defined by contestation and argument. The purpose of this book is to bring clarity to the subject of autism across the full range of its manifestations'--Provided by publisher.
Includes bibliographical references (p. 108-112) and index.
Keywords: Autism